A simultaneous robot service scheme for Multi-users - Lee, Geunjae; Choi, JongSuk; Yun, Sang-Seok; An, Kijin (2015 12TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2015)
In a dialog-based robot service, it is difficult to provide the relevant services for multi-users in a simultaneous manner because multi-users easily interrupt the other's service. In this work, we suggested a service-scheduling scheme for handling the service flows of multi-users. User intention is analyzed by the user's distance and the vocal request obtained by robot sensors. According to the user intention, user service is generated and it is registered in the service queue and then robot provides the service to user with the proposed scheduling policy.